1999
DOI: 10.1007/bf03038899
|View full text |Cite
|
Sign up to set email alerts
|

Prostate preservation by combined external beam and HDR brachytherapy in nodal negative prostate cancer

Abstract: Purpose:The combined external beam-and high-dose rate brachytherapy (HDR-BT) of localized prostate cancer was introduced at Kiel University in 1986. The aim of this intermediate analysis was to judge the Kiel method of localized prostate cancer radiation treatment after ten years experience. Patients and Methods: In the past ten years 174 patients with histological proven localized prostate cancer were subjected to combined tele-/HDR-brachytherapy. Local staging in all of the cases by transrectal ultrasound, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 0 publications
1
25
0
4
Order By: Relevance
“…The median number of patients accrued per institution was 8 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the average was 9 patients. The average monthly accrual for the study was 5.9 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of patients accrued per institution was 8 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the average was 9 patients. The average monthly accrual for the study was 5.9 patients.…”
Section: Resultsmentioning
confidence: 99%
“…(6-10) Kovacs et al reported one of the earliest experiences using HDR brachytherapy boost at University of Kiel. (10)(11)(12) Patients treated were mostly T2b-T3 tumors and high grade tumors. They used a combination of split course external beam radiotherapy and two 15 Gy HDR treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Im Rahmen von Dosiseskalationsstudien sind jedoch tumorkonforme Bestrahlungstechniken unverzichtbar für die Schonung der umliegenden Normalgewebe [11,30]. Auf invasivem Wege kann das mittels Brachy- therapie erreicht werden [1,15]. Eine vielversprechende nichtinvasive Methode stellt die intensitätsmodulierte Strahlentherapie als komplexeste Form der dreidimensional geplanten Strahlentherapie mit Photonen dar [28].…”
Section: Diskussionunclassified
“…These reports resulted in a renaissance for prostate BT. In 1977, Court and Chassangne (18) began treating prostate cancer with after-loading techniques, and since then several reports have been published (13,14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Although the data presented were encouraging, no randomised study has been published, and there are criticisms concerning some of the BT treatment studies (29,30).…”
mentioning
confidence: 99%